A Data Processing Information System for Oil Palm Harvest Results - Febrianza, M; Sanmorino, Ahmad (PT. Lentera Ilmu Publisher, 2026)
Oil palm plantations require accurate and timely harvest data to support effective operational and managerial decision making. However, many plantations still rely on manual data recording methods that are prone to delays, errors, and data inconsistency. This study develops a data processing information system for oil palm harvest results using the Agile–Scrum approach to improve efficiency and data reliability. The system supports structured harvest data entry, automated processing, and real time reporting. Black-box testing was conducted to evaluate functional correctness, and the results show that all tested system functions operated as expected, with a 100% pass rate across key scenarios, including data entry, validation, and report generation. Performance comparison results indicate that the proposed system reduces data entry time by approximately 70%, decreases error rates by up to 85%, and shortens daily report preparation time from several hours to less than five minutes. These results demonstrate that the developed system effectively enhances accuracy, efficiency, and data accessibility in oil palm harvest management.